Foot and mouth disease in and near the Maasai Mara, Kenya - Karlsson, Amanda (2017)
Livestock is very important to the sub-Saharan pastoralists, and the health and wellbeing of the cattle, which are a large portion of the livestock that the farmer keeps, can make or break a family’s livelihood. One important disease in cattle is foot and mouth disease (FMD), a highly contagious disease affecting many species of both cloven–hoofed wildlife and livestock such as cattle. The disease is caused by a virus of the genus Aphthovirus within the Picornaviridae family and is characterized by the formation of vesicles and ulceration in the mouth, on the snout, interdigital space and on the teats. Classical clinical signs include anorexia, excessive salivation and lameness. It is one of the most financially important livestock diseases in the world. In the western world, it is one of the most feared diseases of livestock since it brings great financial losses and can limit the international trade of both livestock and their derived products. This study investigated the prevalence of active foot and mouth disease in three villages (Lemek, Endoinyo Narasha and Mara Rianta) in and around the Maasai Mara national reserve in Kenya. Further, the possible risk factors for FMD transmission were assessed with the help of a questionnaire that was administered to farmers of each investigated herd. The selected villages were all at different distances from the national reserve and have adopted different animal husbandry practices. The proximity of Mara Rianta to the national reserve allow the pastoralists to graze in the parks while in Endonyio Narasha and Lemek, many farmers practice sedentary grazing in fenced lands. In order to find suspected cases of FMD a brief clinical examination of the animals was done. Three animals from each of the 75 farms (25 farms from each of the three different villages) was examined, a total of 225 animals. Animals with suspected active lesions were tested using a lateral flow device (Svanodip FMDV antigen test) to detect FMD viral antigen from vesicular fluid or epithelial cells. In total 27 animals (11.6%) with suspected active lesions were tested and out of these, one was found to be positive. There was no significant difference between the number of suspected active infections in the three different villages, therefore it was not possible to draw any conclusions regarding the potential risk factor of closeness to national park. More than 80% of the farmers were aware of FMD among neighbours. Analysis of the questionnaire yielded a statistically significant negative correlation between the likelihood of finding potential active infection and farmers to report having animals unwilling to walk or stand, which was reported in 19% of the farms. In contrary to that, it was more likely to find animals with suspected active FMD in farms where the farmer had reported seeing blisters in the mouth, snout or hooves, which was reported in 21% of the farms. From this study one can conclude that a good question, in order to find animals with suspected FMD, is whether the farmer has any animals with blisters. This study confirms that FMD circulates in villages surrounding the national reserve Maasai Mara and concludes that more research is necessary which will help devise sustainable control strategies in the area.